An Evaluation of Antimicrobial Efficacy of Steralium, co+steralium, and 5% Sodium Hypochlorite against Enterococcus Faecalis Biofilm Formed on Tooth Substrate: (An in Vitro Study) - Al-Kadhi, Ayad M (Journal of Baghdad College of Dentistry, 2016)
Background: Enterococcus faecalis is emerging as an important endodontic pathogen, which can persist in the environment for extended periods after treatment and may cause endodontic failure. It is known to produce biofilms, a community of bacteria enclosed within a protective polymeric matrix. This study aimed to establish whether the biofilm formation by Enterococcus faecalis can be inhibited with steralium, co+steralium, and 5% sodium hypochlorite in the root surface environment. Materials and Methods: Extracted human teeth were biomechanically prepared, vertically sectioned, placed in the tissue culture wells exposing the root canal surface to E. faecalis to form a biofilm. At the end of the 3rd and 6th weeks, all groups were treated for 10 minutes with the previously mentioned tested solutions and control and were analyzed qualitatively and quantitatively. Results: Qualitative assay with 3-weeks biofilm showed a complete inhibition of bacterial growth with co+steralium and NaOCl, except steralium and saline, which showed presence of bacterial growth. In quantitative analysis, steralium and saline- treated tooth samples have 57.74 ± 5.39* CFU/ml., 140.71 ± 8.49 CFU/ml. respectively. Qualitative assay with 6-week biofilm showed growth when treated with steralium and saline treated tooth samples have 346.0 ± 78.88* CFU/ml., 127.18 ± 17.84 CFU/ml. respectively whereas co+steralium and NaOCl has shown complete inhibition. Conclusions: co+steralium and 5% sodium hypochlorite showed maximum antibacterial activity against E. Faecalis biofilm formed on tooth substrate. co+steralium showed statistically significant antibacterial activity. The use of co+steralium as a root canal irrigant might prove to be advantageous considering the several undesirable characteristics of NaOCl. Key words: Biofilm, E. faecalis, steralium, co+steralium, NaOCl, root canal irrigant.